Potensi Sektor Pertanian dalam Perekonomian Wilayah Provinsi Papua - Yundy Hafizrianda; Ida Ayu Purba Riani (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2023)
This study aims to (1) measure and analyze the contribution of the agricultural sector to the regional economy of Papua Province; and (2) identify and analyze the macro-sectoral potential of the management of the agricultural sector in Papua Province. There are two analytical tools used, namely the LQ Index and Sectoral Classen Typology. Based on the results of data processing with LQ analysis, it was identified that the agricultural sector is the base in Jayapura, Keerom, Sarmi, Mamberamo Raya, Biak Numfor, Supiori, Kepulauan Yapen, and Waropen Regencies. As for Jayapura City, the agricultural sector is not a base because it has an agricultural LQ value of 0.48 < 1. Then, from the Sectoral Classen Typology analysis, it shows that macrosectorally and macrospatially, the management of agricultural natural resources in Papua Province in the future is very prospective for developing regional economies. This is indicated by the typology of the agricultural sector in each region in Papua, which is mostly classified as an advanced and fast-growing sector (Quadrant I) for the future, namely in Sarmi, Keerom, Mamberamo Raya, Supiori, Kepulauan Yapen, and Waropen Regencies. The sectors that are categorized as advanced and fast-growing can be used as prime sectors and priorities for development in the future, both in the short, medium, and long term, in the Province of Papua. Keywords: Agricultural Sector, Economic Base, Sectoral Classen Typology